Assessment of knowledge, attitude and barriers towards pharmacovigilance among physicians and pharmacists of Abbottabad, Pakistan - Syed, Akash; Azhar, Saira; Raza, Muhammad Mohsin; Saeed, Humaira; Jamshed, Shazia Qasim (MDPI, 2018)
Objectives: Pharmacovigilance in Pakistan needs robust preference in terms of implementation and consistent movement of structured approaches. The objective of this study is to explore the knowledge, attitude and barriers towards adverse drug reaction (ADR) reporting among physicians and pharmacists and to explore the encouraging factors of ADR reporting. Methods: The current research was a cross-sectional study design in which a pre-validated questionnaire was administered to physicians and pharmacists in Abbottabad, Pakistan. The study was conducted for two months from January 2016 to February 2016. Results: A total of 194 physicians and pharmacists responded with a response rate of 35.3%. All the respondents either strongly agreed or agreed that ADRs reporting is a part of their duty. Half of the respondents agreed that monitoring of drug safety is important. Around three quarters of respondents (74.2%) stated that they did not report ADRs due to unavailability of reporting forms while 70% cited lack of a proper pharmacovigilance center as one of the key barriers. Half of the respondents (52.2%) did not report due to their insufficient knowledge. A large majority (81.8%) said that they would report ADRs if there is pharmacovigilance center. On the point of incentives, opinion seems to be divided. Slightly less than half (47.8%) cited their wish to have few incentives while the remaining 52.2% either preferred to be neutral or disagreed. Conclusion: Based on the study findings, barriers were mostly related to general unfamiliarity with ADRs reporting guidelines and the non-existence of a pharmacovigilance center. It is highlighted that the regulatory body should carve a niche for a properly functional pharmacovigilance center and initiate educational programs for strengthening knowledge and attitudes towards ADR reporting.